2022
DOI: 10.31577/km.2022.6.387
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat treatments on microstructure and wear behavior of AISI H13 tool steel

Abstract: The influence of quenching and tempering heat treatments on the microstructure and wear behavior of AISI H13 tool steel was investigated. The austenitization was carried out at 1050 • C. After austenitization, oil quenching, single tempering, and sequential double tempering treatments were carried out. The microstructure, hardness, and wear behavior of the samples were studied. Three different types of carbide particles, M23C6, MC, and M7C3, were determined in the microstructure. The sample, subjected to quenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The strip shape or rod like carbides and elliptical shape or coarse shape indicated by the brown arrow are chromium rich M7C3 carbides and M23C6 carbides as presented in the literature, the chromium diffuses at the grain boundaries very rapidly so the grain coarsening is observed with chromium rich M23C6 carbides [23]. The fine spherical shape or square type indicated by the red arrow symbolizes vanadium rich MC type carbides as described in the literature [24][25][26][27] and typically it varies from 130nm to 170nm. The carbide size for repeated tempering cycles was analyzed and obtained values are presented in table 8 which indicates that as the tempering time varies from 2hr to 8hr the carbide coarsening occurs along the grain boundaries and as well as gets precipitated inside the laths of the martensite as shown in figure 7 a) and c).…”
Section: Carbide Size Analysismentioning
confidence: 82%
“…The strip shape or rod like carbides and elliptical shape or coarse shape indicated by the brown arrow are chromium rich M7C3 carbides and M23C6 carbides as presented in the literature, the chromium diffuses at the grain boundaries very rapidly so the grain coarsening is observed with chromium rich M23C6 carbides [23]. The fine spherical shape or square type indicated by the red arrow symbolizes vanadium rich MC type carbides as described in the literature [24][25][26][27] and typically it varies from 130nm to 170nm. The carbide size for repeated tempering cycles was analyzed and obtained values are presented in table 8 which indicates that as the tempering time varies from 2hr to 8hr the carbide coarsening occurs along the grain boundaries and as well as gets precipitated inside the laths of the martensite as shown in figure 7 a) and c).…”
Section: Carbide Size Analysismentioning
confidence: 82%
“…The research shows that the grain size of H13 die steel is obviously reduced and that the open circuit potential is increased after conventional heat treatment and then cryogenic treatment at −185 • C; this is beneficial to the improvement of the corrosion resistance of the material and can be used in an environment with high mechanical stress and corrosion. Melika [4] studied the effect of quenching and tempering treatment on the microstructure and wear resistance of H13 hot-work die steel. The experiment showed that the hardness of H13 hot-work die steel is greatly improved after austenitizing at 1050 • C and oil quenching, but slightly decreases after quenching at 530 • C in a single tempering treatment.…”
Section: Introductionmentioning
confidence: 99%
“…3 raised the temperature to 1040 • C and kept the temperature for 90 min;4 vacuum gas quenched to a temperature below 80 • C for furnace discharge;5 deep cooling temperature of −80 • C, insulation for 90 min, cooled to around −30 • C and taken out of furnace and left at room temperature, as shown in Figure 3b. (3) H3 (vacuum oil quenching-deep cooling process): 1 Entered the furnace at room temperature, raised the temperature to 650 • C, and kept the temperature for 150 min; 2 raised the temperature to 850 • C and kept the temperature for 120 min; 3 raised the temperature to 1040 • C and kept the temperature for 90 min; 4 vacuum oil quenched to a temperature below 40 • C for furnace discharge; 5 deep cooling temperature of −80 • C, insulation for 90 min, cooled to around −30 • C and taken out of furnace and left at room temperature, as shown in Figure 3c.…”
mentioning
confidence: 99%